2008
DOI: 10.1007/s11664-008-0581-6
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Mesa Shaped InGaN-Based Light-Emitting Diodes Through a Photoelectrochemical Process

Abstract: InGaN-based light-emitting diodes (LEDs) were fabricated to have a higher light extraction through the photoelectrochemical (PEC) mesa shaping process. After the PEC selective wet oxidation and wet etching processes, stable and controllable crystallographic etching planes were formed as p-type GaN {1011} planes and n-type GaN {1010} planes included at an angle of 27 deg. The ever-present cone-shaped structure of a PEC-treated LED has a larger light scattering area and higher light extraction cones on the mesa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…It has been shown that high extraction efficiency in GaN-based LEDs can be obtained by several approaches, including chip shaping, surface roughness, patterned sapphire substrate, photonics crystals, flip-chip packaging and conductive omni-directional reflectors, have been extensively studied. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] In general, GaN-based LEDs are grown on the sapphire substrates, because there is no large substrate available for GaN heteroepitaxial growth. The order of the dislocation density was 108-1010cm-2 has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that high extraction efficiency in GaN-based LEDs can be obtained by several approaches, including chip shaping, surface roughness, patterned sapphire substrate, photonics crystals, flip-chip packaging and conductive omni-directional reflectors, have been extensively studied. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] In general, GaN-based LEDs are grown on the sapphire substrates, because there is no large substrate available for GaN heteroepitaxial growth. The order of the dislocation density was 108-1010cm-2 has been reported.…”
Section: Introductionmentioning
confidence: 99%